Second metabolites and antioxidant, antimicrobial, anticancer activities of Helicteres hirsuta root extract - Dung, Diem Thi Thuy; Trang, Trinh Huyen; Linh, Le Thi Khanh; Tan, Dao Van; Hoa, Le Thi Phuong (Academia Journal of Biology, 2018)
Helicteres hirsuta Lour., particularly its stems and leaves have been used in Vietnamese traditional medicine to cure furuncles, dysentery, measles and flu. In this study, we examined biological activities of 5 fractions from methanol extract of H. hirsuta roots. The results showed that ethyl acetate fraction has the highest content of phenolic and flavonoid compounds (220.9 ± 15.67 mg GAE, gallic acid equivalents/g dry weight and 23.03 ± 0.97 mg QE, quercetin equivalents/g dry weight, respectively). Fractions from H. hirsuta roots exhibited antioxidant, antibacterial and anticancer activities. Ethyl acetate fraction showed the strongest antioxidant activity through 1,1diphenyl-2-picrylhydrazyl (DPPH) scavenging capacity (half-maximal inhibitory concentration, IC50 value of 0.117 ± 0.023 mg/ml). Ethyl acetate fraction of roots also showed the strongest reducing power (0.071 ± 0.009 mg/ml) and cytotoxicity on human KB cell lines (IC50= 3.23 μg/ml). Besides, fractions from H. hirsuta roots had high inhibitory activity against Gram-positive bacteria namely Staphylococcus aureus and Lactobacillus fermentum. The results suggest potential exploitation of bioactive compounds from H. hirsuta roots especially ethyl acetate fraction and its application in medicine and pharmacy. This is the first report on second metabolite composition and biological activities of H. hirsuta roots.